Use of Medicinal Plants and Its Association with Health Literacy in the General Population of Iran During the COVID-19 Pandemy: a Web-Based Cross-Sectional Survey - Farid Dabaghian; Maryam Hasanpour; Saman Maroufizadeh; Mohammad Hossein Joulani; Mahnaz Khanavi* (Iranian Society of Pharmacognosy, 2023)
Background and objectives: During health crises like COVID-19, people with different health conditions turn to traditional/herbal remedies, which can affect their health status. This study aimed to determine medicinal plant consumption and its association with health literacy during the COVID-19 pandemic in Iran. Methods: This web-based cross-sectional study involved 1242 Iranians aged 18 to 65. Data were collected using the Iranian Health Literacy Questionnaire (IHLQ), COVID-19-related variables, and a socio-demographic information questionnaire, analyzed by simple and multiple logistic regression analyses using SPSS 16.0. Results: It was found that 51.4% (n=638) of participants had used medicinal plants and herbal products, with a mean Health Literacy (HL) score of 76.16. Thyme (50.6%), ginger (34.9%), and cinnamon (24.4%) were the most commonly used plants; the most popular methods were infusion (78.3%) and decoction (32.2%). According to the adjusted analysis, the use of medicinal plants was significantly associated with being older (odds ratio (OR)=1.85, 95% confidence interval (CI):1.14-3.00), having contact with suspected/confirmed COVID-19 cases (OR=1.94, 95% CI:1.39-2.71), and having family members, friends, and/or relatives infected with COVID-19 (OR=1.37, 95% CI:1.00-1.88). Also, people who consulted with a physician or pharmacist before using medicinal plants had statistically higher mean HL scores than those who did not (p<0.001), as do those who consider potential interactions with other medications or medicinal plants (p<0.001). Conclusion: Considering that at least half of the people used medicinal plants during the COVID-19 outbreak, providing accurate information by regulatory organizations on medicinal plants, their potential side effects, and interactions, especially during times of crisis, seems to be urgent.